Identification of Social Capital Bonding Inter Trader and Bank Thithil (Study Case in Blimbing Traditional Market, Malang City) - Hidayati, Bunga; Suman, Agus; Manzilati, Asfi (International Journal of Social and Local Economic Governance, 2016)
In traditional market activity, economic actors who are in it not only traders or buyers. But there are also other economic actors who became part of the traders capital resources is loan shark. In terms of Java, loan shark referred to as "Bank Thithil". The purpose of this study was to identify the bonding social capital (interaction of individuals within the group) on interactions inter-traders and inter Bank Thithil. By use qualitative method with phenomenological approach, the results shows that bonding social capital at the micro network between traders to collective action to loan contract with Bank Thithil. While elements of social capital of trust that is infectious, micro and norms make Â network of interaction between the traders and Bank Thithil increasingly exist. Moreover, capital support from Bank Thithilâ€™s family can reduce transaction costs and improve the existence of Bank Thithil.